Development of a recombinase-aided amplification combined with a lateral flow dipstick assay for rapid detection of H7 subtype avian influenza virus - Zhang, Fuyou; Shang, Jiajing; Luo, Juan; Yin, Xin; Yu, Xiaohui; Jiang, Wenming; Li, Jinping; Yuan, Liping; Hou, Guangyu; Liu, Hualei; Li, Yang (Frontiers in Microbiology, 2023)
Avian influenza viruses (AIV) pose a significant persistent threat to the public health and safety. It is estimated that there have been over 100 outbreaks caused by various H7 subtypes of avian influenza viruses (AIV-H7) worldwide, resulting in over 33 million deaths of poultry. In this study, we developed a recombinase-aided amplification combined with a lateral flow dipstick assay for the detection of hemagglutinin (HA) genes to provide technical support for rapid clinical detection of AIV-H7. The results showed that the assay can complete the reaction within 30 minutes at a temperature of 39°C. Specificity tests demonstrated that there was no crossreactivity with other common poultry pathogens, including Newcastle disease virus (NDV) and infections bronchitis virus (IBV). The detection limit of this assay was 1×10 1 copies/μL, while RT-qPCR method was 1×10 1 copies/μL, and RT-PCR was 1× 10 2 copies/μL. The κ value of the RT-RAA-LFD and RT-PCR assay in 132 avian clinical samples was 0.9169 (p<0.001). These results indicated that the developed RT-RAA-LFD assay had good specificity, sensitivity, stability and repeatability and may be used for rapid detection of AIV-H7 in clinical diagnosis.